Implementation of guidance and counselling in secondary schools in Chinhoyi urban - Gudyanga, Ephias; Wadesango, N.; Manzira, L. R.; Gudyanga, Anna (Kamla-Raj, 2016)
The study endeavoured to find out the current contribution of head teachers and teachers in the implementation of guidance and counselling curriculum in Chinhoyi. The study adopted mixed methodology approach. Questionnaires and interviews were used to collect data from participants about their experiences and opinions. A sample of four head teachers and forty (40) teachers was used in this study. Content analysis and statistical analysis were used to analyse data. The study established that only one school among the sampled schools was implementing Guidance and Counselling programme although other schools claimed to be implementing the programme. The government should provide trained and competent Guidance and Counselling co-ordinators so that they would be posted to various districts in the country.